2008
DOI: 10.1371/journal.pone.0002728
|View full text |Cite
|
Sign up to set email alerts
|

Forty Years Trends in Timing of Pubertal Growth Spurt in 157,000 Danish School Children

Abstract: BackgroundEntering puberty is an important milestone in reproductive life and secular changes in the timing of puberty may be an important indicator of the general reproductive health in a population. Too early puberty is associated with several psychosocial and health problems. The aim of our study was to determine if the age at onset of pubertal growth spurt (OGS) and at peak height velocity (PHV) during puberty show secular trends during four decades in a large cohort of school children.Methods and Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
128
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(151 citation statements)
references
References 43 publications
21
128
1
1
Order By: Relevance
“…Pubertal development in Danish-born girls is late compared to studies from USA [52], but is in accordance with recent studies from Northern Europe [11,55]. Even though a long-standing halt in the secular trend in Denmark has been reported [11,56], recent data suggest earlier pubertal maturation [57,58]. …”
Section: Discussionsupporting
confidence: 83%
“…Pubertal development in Danish-born girls is late compared to studies from USA [52], but is in accordance with recent studies from Northern Europe [11,55]. Even though a long-standing halt in the secular trend in Denmark has been reported [11,56], recent data suggest earlier pubertal maturation [57,58]. …”
Section: Discussionsupporting
confidence: 83%
“…The fact that hypertensive and normotensive males were of same adult height and the association for heightvelocity was confined to the period between 11 and 13 years strongly suggests that the association may be driven by relatively early onset of puberty. 28 A British study assessing pubertal development at 15 years by medical examination observed a positive association between early onset of puberty and adult blood pressure for males born in the 1950s. 29 The association was also stable with respect to adult body size, and the observed effect size was similar to our study (5 mm Hg for SBP).…”
Section: Discussionmentioning
confidence: 99%
“…Even though studies have shown a downward trend in the ages of physical onset of puberty worldwide (2,8), this trend is more pronounced for initial onset events and less so for age at menarche in girls, a relatively late event and occurring only after substantial hormone stimulation. We estimate the age at hormonal onset of puberty and explore the extent to which weight gain affects the timing.…”
mentioning
confidence: 91%